2018
DOI: 10.1111/jir.12510
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes of health care professionals toward people with intellectual disability: a comparison with the general population

Abstract: In addition to providing general knowledge about ID and the specific health care needs of individuals with ID, training programmes should also promote interactions with this population. Further studies are needed to document HCPs' pro-inclusion attitudes toward people with ID and to assess the impact of interventions on these attitudes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 50 publications
2
15
0
Order By: Relevance
“…In other research (Morin et al . ), the ATTID long form was able to differentiate health care professionals from the general population, showing that the professionals had more positive attitudes towards people with ID and that the more contact they had with them, the more positive their attitudes were.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…In other research (Morin et al . ), the ATTID long form was able to differentiate health care professionals from the general population, showing that the professionals had more positive attitudes towards people with ID and that the more contact they had with them, the more positive their attitudes were.…”
Section: Discussionmentioning
confidence: 96%
“…The original ATTID has been used in recently published studies (Morin et al . , , ; Murch et al . ; Phillips et al .…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies also showed that healthcare professionals who reported less experience expressed more discomfort in dealing with persons with disabilities. 9,11 The limitations of this study should be noted. The questionnaire was administered to healthcare professionals in tertiary university hospitals.…”
Section: Domainmentioning
confidence: 88%
“…3,4 These attitudes or actions should be minimized or removed from people working in the healthcare system, because they can negatively influence the quality of medical care, especially in rehabilitation settings. 1,[5][6][7][8][9][10][11] Training or education programs to improve these attitudes require measurement tools to identify the initial status and changes after the interventions. 6 Moreover, understanding healthcare professionals' attitudes toward persons with disability by using these tools and identifying the factors associated with the attitudes could be helpful in designing the educational programs.…”
Section: Introductionmentioning
confidence: 99%
“…We can, however, extrapolate from them medical attitudes regarding ID-especially when they are confirmed by research likeKlein (2011) andSkotko (2011). Also seeMorin (2018),Ormond (2003), Pelleboer-Gunnink (2017), andRyan and Scior (2014).…”
mentioning
confidence: 90%